A Large Pericardial Effusion Culminating in Left Lung Collapse - Amin, Hina (Cureus, 2019)
Pericardial effusion is characterized by excess fluid accumulation in the pericardium. It can be asymptomatic or silent when the effusion is trivial in size or develops slowly. On the other hand, large rapidly developing effusions may present with hemodynamic instability or tamponade. In rare circumstances when a large effusion develops over a period of time, it may cause compression atelectasis of the surrounding bronchi and lung. We describe the case of a 70-year-old female who presented with acute respiratory insufficiency due to left lung collapse secondary to large pericardial effusion. To our knowledge, this is an extremely rare complication of large pericardial effusion.